Effects of gamma ray on some molecular characteristics of in vitro regenerated Gerbera jamesonii Bolus (Bangladesh Journal of Botany, 2011)
DOI: 10.3329/bjb.v39i2.7490Bangladesh J. Bot. 39(2): 207-214, 2010 (December)